Using a Combination Approach in Imparting Effective Telephone Referral Skills to Emergency Medicine Residents in Qatar: A Pilot Study - Khalid Bashir (9300293) (2020)
Background Appropriate and timely feedback is essential in improving communication skills and is endorsed as a core competency of emergency medicine residency (EMR) education by the Accreditation Council for Graduate Medical Education. Aim The study aimed to improve the telephone referral skills through a structured feedback session using ISBAR and to gauge residents’ opinions about this approach. Methods This was a pilot, educational project that included emergency medicine residents in current training program from October 2018 to March 2019. A senior faculty observed and audiotaped the telephone referral of the residents during a clinical shift. Personalized feedback was provided immediately after the consultation based on the ISBAR tool. The resident’s opinion was transcribed by the faculty. Results Seventeen residents agreed to participate, but 14 (3 female and 11 male) were able to complete the study. Three residents, all male, could not complete the study due to busy clinical shifts. Thirteen (out of 14) really liked this method of feedback “eye opener”, “really helped me to reflect” and 10 indicated to self-record some of their future consultations for self-improvement. Thirteen preferred this form of feedback as compared to conventional feedback. One resident disliked this approach as she was extremely nervous during direct observation and audio recording. Conclusion A combination approach of direct observations and audio recordings may be a useful pedagogy in teaching effective telephone referral skills to ED residents. Other Information Published in: Advances in Medical Education and Practice License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.2147/amep.s236802